Bouche en cœur, battement de cils et tête à l’envers : rencontres et flirts à Nouakchott (Mauritanie) - Céline Lesourd (L’Année du Maghreb)
In Mauritania, where females are supposed to be subordinate to males, we in fact observe a complex diplomacy of relations between the sexes. The analysis of several mixed spaces that are available to the upper classes in the Mauritanian capital, Nouakchott, show that women can be demanding with men and inverse roles: they require presents, attention, patience; they enjoy fuelling male rivalry and one-upmanship. These female manipulations must nonetheless follow certain codes; permanently wavering between private and public, there is a difference between what must be seen and what can be seen, between what can be told and what we must remain untold.